Shame and humiliation : presidential decision making on Vietnam - Steinberg, Blema S. (McGill-Queen's University Press, 1996)
Steinberg focuses on the narcissistic personality, identifying it as intensely self-involved and preoccupied with success and recognition as a substitute for parental love. She asserts that narcissistic leaders are most likely to use force when they fear being humiliated for failing to act and when they need to restore their diminished sense of self-worth. Providing case studies of Johnson, Nixon, and Eisenhower, Steinberg describes the childhood, maturation, and career of each president, documenting key personality attributes, and then discusses each one's Vietnam policy in light of these traits. She contends that Johnson authorized the bombing of Vietnam in part because he feared the humiliation that would come from inaction, and that Nixon escalated U.S. intervention in Cambodia in part because of his low sense of self-esteem. Steinberg contrasts these two presidents with Eisenhower, who was psychologically secure and was, therefore, able to carry out a careful and thoughtful analysis of the problem he faced in Indochina. Shame and Humiliation reveals how personality traits affect our perception of reality and offers a powerful demonstration of the impact of psychodynamics on presidential decision making.